2020
DOI: 10.1093/mnras/staa677
|View full text |Cite
|
Sign up to set email alerts
|

X-ray properties of the X-CLASS-redMaPPer galaxy cluster sample: the luminosity–temperature relation

Abstract: This article presents the results of a spectroscopic analysis of the X-CLASS-redMaPPer (XC1-RM) galaxy cluster sample. X-CLASS is a serendipitous search for clusters in X-ray wavebands based on the XMM–Newton archive, whereas redMaPPer is an optical cluster catalogue derived from the Sloan Digital Sky Survey (SDSS). The present sample comprises 92 X-ray extended sources identified in optical images within 1 arcmin separation. The area covered by the cluster sample is ∼ 27 deg2. The clusters span a wide redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Enormous amounts of energy released by a fraction of the SMBH population, in the form of radiative winds, energetic jets, and other mechanisms (Fabian 2012;King & Pounds 2015;Harrison et al 2018;Roy et al 2021), influence several properties of the SMBH host galaxies (e.g., Dressler & Richstone 1988;Kauffmann & Haehnelt 2000;Ferrarese & Merritt 2000;Gebhardt et al 2000;Graham et al 2001;Häring & Rix 2004;Cattaneo et al 2009;Kormendy & Ho 2013;Salviander et al 2015;Fiore et al 2017;Mutlu-Pakdil et al 2018;Schutte et al 2019;de Nicola et al 2019;Marsden et al 2020). Some of the other signatures of AGN feedback involve: a reduced star formation rate in host galaxies (e.g., Vitale et al 2013;Costa et al 2015;Harrison 2017), the absence of cooling flows (e.g., David et al 2001;Peterson et al 2003), or the change in slope of the L X -T relation in galaxy clusters and groups (e.g., Andersson et al 2009;Maughan et al 2012;Molham et al 2020). Despite these series of observational results, a full theoretical understanding of how the energy released from the black hole couples to its surrounding medium, a phenomenon termed active galactic nuclei (AGN) feedback, is yet to arise (e.g., Silk & Rees 1998;Nath & Roychowdhury 2002;Fabian 2012;Li et al 2018;Heinrich et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Enormous amounts of energy released by a fraction of the SMBH population, in the form of radiative winds, energetic jets, and other mechanisms (Fabian 2012;King & Pounds 2015;Harrison et al 2018;Roy et al 2021), influence several properties of the SMBH host galaxies (e.g., Dressler & Richstone 1988;Kauffmann & Haehnelt 2000;Ferrarese & Merritt 2000;Gebhardt et al 2000;Graham et al 2001;Häring & Rix 2004;Cattaneo et al 2009;Kormendy & Ho 2013;Salviander et al 2015;Fiore et al 2017;Mutlu-Pakdil et al 2018;Schutte et al 2019;de Nicola et al 2019;Marsden et al 2020). Some of the other signatures of AGN feedback involve: a reduced star formation rate in host galaxies (e.g., Vitale et al 2013;Costa et al 2015;Harrison 2017), the absence of cooling flows (e.g., David et al 2001;Peterson et al 2003), or the change in slope of the L X -T relation in galaxy clusters and groups (e.g., Andersson et al 2009;Maughan et al 2012;Molham et al 2020). Despite these series of observational results, a full theoretical understanding of how the energy released from the black hole couples to its surrounding medium, a phenomenon termed active galactic nuclei (AGN) feedback, is yet to arise (e.g., Silk & Rees 1998;Nath & Roychowdhury 2002;Fabian 2012;Li et al 2018;Heinrich et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Giles et al (2017) estimated that for their statistically complete sample of 34 X-ray galaxy clusters, the luminosity is ∼ 2.2 times higher for a given mass and a flatter relation is noted if selection effect is not taken into account in the 𝐿-𝑀 relation. Using a simplified approach, Molham et al (2020) also found their measured bias-uncorrected 𝐿-𝑇 relation of their X-ray-optical sample is biased to a steeper slope and higher normalization. As a result, not taking into account selection bias may have a noticeable impact on the measured scaling relations.…”
Section: Discussionmentioning
confidence: 94%
“…However, a plethora of studies report steeper L X − T (B ∼ 2.5) and L bol − T (B ∼ 3.0) relations compared to their selfsimilar predictions (e.g., Pratt et al 2009;Eckmiller et al 2011;Maughan et al 2012;Hilton et al 2012;Kettula et al 2015;Lovisari et al 2015;Zou et al 2016;Giles et al 2016;Molham et al 2020).…”
Section: X -T and L Bol -T Relationsmentioning
confidence: 96%